Strategy for Improving MSMEs Performance Through Stakeholder Involvement - Erni Yuningsih; Sri Harini; Endang Silaningsih (Indonesian Journal of Business Analytics, 2022)
This study aims to identify MSMEs problems, identify internal and external factors, and recommend alternative strategies through stakeholder involvement. This research uses a participatory approach. Data obtained in the form of primary through observation, depth interviews, and FGD. Secondary data was obtained from other sources. Analyzing using IFAS, EFAS and SWOT analysis. Based on the IFAS EFAS score, the competitive ability of MSMEs is classified as moderate. The right strategy is to implement a growth strategy through horizontal integration. In contrast, the alternative approaches are institutional empowerment, increased development, intensive engagement with stakeholders, increased access to funding sources, marketing network development, conducive climate, improvement of entrepreneurship programs, improvement of production and information technology.